Foldable display surface protective film
The surface protection film for folding displays, with its specific polyester film and layered structure, addresses the issue of deformation and image distortion in conventional films, providing enhanced durability and image quality for foldable displays.
Patent Information
- Application Number
- JP2025004291
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2038-04-24
AI Technical Summary
Conventional surface protection films for folding displays deform and cause image distortion when repeatedly folded, which affects the visibility and portability of foldable display devices.
A surface protection film for folding displays is developed, featuring a polyester film with a thickness of 10 to 75 μm and an intrinsic viscosity of 0.65 to 1.0 dl/g, combined with an adhesive layer on one side and a hard coat layer on the other, which is biaxially oriented to enhance mechanical properties and resistance to deformation.
The film effectively prevents deformation and image distortion after repeated folding, ensuring that the display maintains high image quality and portability, making it suitable for use in foldable display devices.
Smart Images

Figure 2025039796000001 
Figure 2025039796000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a surface protective film for a foldable display that is attached to the surface of a foldable display equipped in a mobile terminal device or the like, and relates to a surface protective film for a foldable display that is unlikely to cause image distortion due to deformation of the surface protective film located on the surface, even when the display is folded repeatedly. [Background technology]
[0002] As mobile terminal devices become thinner and lighter, smartphones and other mobile terminal devices are becoming more and more popular. While mobile terminal devices are required to have a variety of functions, they are also required to be convenient. For this reason, the mobile terminal devices that are currently in use must be able to perform simple operations with one hand, and must have a small screen size of around 6 inches, since they are assumed to be stored in a pocket or the like.
[0003] On the other hand, tablet devices with screen sizes of 7 to 10 inches are highly functional and can be used not only for video content and music, but also for business purposes, drawing, reading, etc. However, they cannot be operated with one hand, are less portable, and have issues with convenience.
[0004] To achieve these goals, a method has been proposed of connecting multiple displays together to make them more compact; however, this method has not become widespread because it leaves behind a bezel, which results in the image being cut off and reduced visibility.
[0005] In recent years, mobile terminals incorporating flexible displays and foldable displays have been proposed, which provide a large-screen display without interruption to the image and are convenient to carry around.
[0006] The display surface of mobile terminal devices is generally made of glass or a hard-coated film, which makes it scratch-resistant; however, scratches will inevitably occur when rubbed against stones or metal, so in practice an adhesive surface protection film is later affixed to the display surface (see Patent Document 1).
[0007] Here, for displays and mobile terminal devices that do not have a conventional folding structure, some of the surface protection films for the displays are made of inexpensive, impact-resistant polyester films. On the other hand, in folding displays, the parts that correspond to certain folding parts are repeatedly folded, so the films in those parts deform over time, and when a general polyester film is used, there are problems such as distorting the images displayed on the display. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2010-228391 A Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention seeks to solve the problems associated with conventional surface protection films for displays as described above, and to provide a surface protection film for a foldable display that does not pose a risk of distortion of the image displayed on the folded portion after repeated folding. [Means for solving the problem]
[0010] That is, the present invention comprises the following: 1. A surface protection film for a folding display, comprising a polyester film having a thickness of 10 to 75 μm and an intrinsic viscosity of 0.65 to 1.0 dl / g and an adhesive layer on one side thereof. 2. A surface protection film for a foldable display according to claim 1, in which a hard coat layer is laminated on the side of the polyester film opposite to the side having the adhesive layer. 3. A surface protection film for a folding display according to claim 1 or 2, wherein the polyester film is a biaxially oriented polyethylene terephthalate film. Effect of the Invention
[0011] The surface protective film for a folding display of the present invention is one that does not cause image distortion at the folded portion of the display because the surface protective film located on the surface of the folding display does not deform after repeated folding. A mobile terminal device equipped with such a folding display provides beautiful images, is highly functional, and is convenient in terms of portability, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] (display) The display in the present invention generally refers to a display device, and the types of displays include LCD, organic EL display, inorganic EL display, LED, FED, etc., but LCD, organic EL, and inorganic EL, which have a bendable structure, are preferred. In particular, organic EL and inorganic EL, which can reduce the layer structure, are particularly preferred, and organic EL, which has a wide color gamut, is even more preferred.
[0013] (Foldable display) A foldable display is preferably a single continuous display that can be folded in half when carried, reducing its size by half and improving portability. At the same time, it is desirable for the display to be thin and lightweight.
[0014] (Organic EL) The general configuration of an organic EL display consists of an organic EL layer consisting of an electrode / electron transport layer / light-emitting layer / hole transport layer / transparent electrode, a retardation plate to improve image quality, and a polarizing plate.
[0015] (Mobile terminal device with touch panel) When an organic EL display is used in a mobile terminal device having a touch panel, a touch panel module is placed on top of the organic EL display or between the organic EL layer and the retardation plate. In this case, if an impact is applied from above, the circuits of the organic EL and the touch panel may be broken, so it is common to attach a surface protection film during normal use. It is preferable that the surface protection film has a hard coat layer laminated on the surface side.
[0016] As the surface protection film, any film having high light transmittance and low haze, such as a polyimide film, a polyester film, a polycarbonate film, an acrylic film, a TAC film, or a cycloolefin polymer film, can be used. Among these, a polyester film having high impact resistance and which can be produced inexpensively is preferred.
[0017] In the present invention, the polyester film may be a single-layer film made of one or more polyester resins, or when two or more types of polyester are used, it may be a multilayer film or an ultra-multilayer laminate film having a repeating structure.
[0018] Examples of polyester resins include polyester films made of polyethylene terephthalate, polybutylene terephthalate, polyethylene-2,6-naphthalate, or copolymers mainly composed of the components of these resins. Among these, biaxially stretched polyethylene terephthalate films are particularly preferred in terms of mechanical properties, heat resistance, transparency, cost, etc.
[0019] When a polyester copolymer is used for the base film, examples of the dicarboxylic acid component of the polyester include aliphatic dicarboxylic acids such as adipic acid and sebacic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalenedicarboxylic acid; and polyfunctional carboxylic acids such as trimellitic acid and pyromellitic acid. Examples of the glycol component include fatty acid glycols such as ethylene glycol, diethylene glycol, 1,4-butanediol, propylene glycol, and neopentyl glycol; aromatic glycols such as p-xylene glycol; alicyclic glycols such as 1,4-cyclohexanedimethanol; and polyethylene glycols having an average molecular weight of 150 to 20,000. The mass ratio of the copolymerization components of the preferred copolymer is less than 20% by mass. When it is less than 20% by mass, the film strength, transparency, and heat resistance are maintained, which is preferable.
[0020] In addition, in the production of the base film, the intrinsic viscosity of at least one type of resin pellet is preferably in the range of 0.65 to 1.0 dl / g. When the intrinsic viscosity is 0.65 dl / g or more, the obtained film is less likely to deform after repeatedly folding, and there is no risk of image quality being deteriorated, which is preferable. On the other hand, when the intrinsic viscosity is 1.00 dl / g or less, the filtration pressure of the molten fluid does not increase too much, and film production can be easily and stably operated, which is preferable.
[0021] Regardless of whether the film is a single-layered or laminated film, the intrinsic viscosity of the film is preferably 0.65 dl / g or more. More preferably, it is 0.68 dl / g or more. If it is 0.65 dl / g or more, sufficient bending resistance effect can be obtained. On the other hand, a film having an intrinsic viscosity of 1.00 dl / g or less is preferable because it can be produced with good operability.
[0022] The thickness of the polyester film is preferably 10 to 75 μm, and more preferably 25 to 75 μm. When the thickness is 10 μm or more, the pencil hardness of the hard coat layer is improved when the hard coat layer is laminated on the opposite side of the adhesive layer, and when the thickness is 75 μm or less, it is advantageous for weight reduction and is excellent in flexibility, processability, handleability, etc.
[0023] The surface of the polyester film of the present invention may be smooth or may have irregularities, but since the film is used for protecting the surface of a display, it is not preferable that the film has low light transmittance.
[0024] The unevenness can be formed by blending a filler with the polyester resin or by coating a coat layer containing a filler during the film formation.
[0025] The method of blending the particles into the polyester film can be a known method. For example, the particles can be added at any stage of polyester production, but preferably, the particles can be added as a slurry dispersed in ethylene glycol or the like at the stage of esterification, or after the completion of the transesterification reaction, and before the start of the polycondensation reaction, to proceed with the polycondensation reaction. The particles can also be blended with a slurry of the particles dispersed in ethylene glycol or water or the like and the polyester raw material using a vented kneading extruder, or with a method of blending dried particles and the polyester raw material using a kneading extruder.
[0026] Among them, a method is preferred in which aggregated inorganic particles are homogeneously dispersed in a monomer liquid that will become a part of the polyester raw material, and then the filtered product is added to the remainder of the polyester raw material before, during, or after the esterification reaction. According to this method, since the monomer liquid has a low viscosity, homogeneous dispersion of the particles and highly accurate filtration of the slurry can be easily performed, and when added to the remainder of the raw material, the dispersibility of the particles is good and new aggregates are unlikely to be generated. From this viewpoint, it is particularly preferred to add to the remainder of the raw material in a low temperature state before the esterification reaction.
[0027] In addition, the number of protrusions on the film surface can be further reduced by a method in which, after obtaining a polyester containing particles in advance, the pellets are mixed and extruded with pellets not containing particles (master batch method).
[0028] The polyester film may contain various additives, such as antistatic agents, UV absorbers, and stabilizers, within the limits of maintaining light transmittance.
[0029] The total light transmittance of the polyester film is preferably 85% or more, and more preferably 87% or more. A transmittance of 85% or more is preferable because sufficient visibility can be ensured. The higher the total light transmittance of the polyester film, the better, but it may be 99% or less, or 97% or less.
[0030] The surface of the polyester film of the present invention may be subjected to a treatment for improving adhesion to a resin forming an adhesive layer, a hard coat layer, or the like.
[0031] Examples of the surface treatment method include roughening treatment using sandblasting or solvent treatment, and oxidation treatment such as corona discharge treatment, electron beam irradiation treatment, plasma treatment, ozone or ultraviolet irradiation treatment, flame treatment, chromic acid treatment, or hot air treatment, and any of these methods can be used without any particular limitation.
[0032] In addition, the adhesion can be improved by an adhesion improving layer such as an easy-adhesion layer. The easy-adhesion layer can be made of any resin such as an acrylic resin, a polyester resin, a polyurethane resin, or a polyether resin, and can be formed by a general coating method, preferably a so-called in-line coating method.
[0033] The above-mentioned polyester film can be produced, for example, through a polymerization step in which inorganic particles are homogeneously dispersed in a monomer liquid that becomes a part of the polyester raw material, the monomer liquid is filtered, and then the dispersion is added to the remainder of the polyester raw material to polymerize the polyester, and a film formation step in which the polyester is melt-extruded through a filter into a sheet, which is cooled and stretched to form a polyester film.
[0034] Next, a method for producing a biaxially stretched polyester film preferably used in the present invention will be described in detail using an example in which polyethylene terephthalate (hereinafter, sometimes referred to as PET) pellets are used as the raw material for the film, but the present invention is not limited thereto. In addition, the number of layers, such as a single layer structure or a multilayer structure, is not limited thereto.
[0035] After mixing and drying PET pellets in a predetermined ratio, the mixture is fed to a known melt lamination extruder, extruded from a slit die into a sheet, and cooled and solidified on a casting roll to form an unstretched film. In the case of a single layer, one extruder is sufficient, but in the case of producing a film with a multilayer structure, two or more extruders, two or more manifolds or merging blocks (e.g., merging blocks having a rectangular merging portion) are used to laminate multiple film layers constituting each outermost layer, and a sheet of two or more layers is extruded from a die and cooled on a casting roll to form an unstretched film.
[0036] In this case, it is preferable to perform high-precision filtration to remove foreign matter contained in the resin at any location where the molten resin is kept at about 280° C. during melt extrusion. The filter material used for high-precision filtration of the molten resin is not particularly limited, but a filter material made of sintered stainless steel is preferable because it has excellent performance in removing aggregates and high-melting organic matter mainly composed of Si, Ti, Sb, Ge, and Cu.
[0037] Furthermore, the filtration particle size (initial filtration efficiency 95%) of the filter medium is preferably 20 μm or less, particularly preferably 15 μm or less. If the filtration particle size (initial filtration efficiency 95%) of the filter medium exceeds 20 μm, foreign matter with a size of 20 μm or more cannot be sufficiently removed. By using a filter medium with a filtration particle size (initial filtration efficiency 95%) of 20 μm or less to perform high-precision filtration of molten resin, productivity may decrease, but it is preferable to obtain a film with few protrusions due to coarse particles.
[0038] Specifically, for example, PET pellets are thoroughly vacuum-dried, then fed to an extruder, melt-extruded into a sheet at about 280°C, and cooled and solidified to form an unstretched PET sheet. The unstretched sheet obtained is stretched 2.5 to 5.0 times in the longitudinal direction with a roll heated to 80 to 120°C to obtain a uniaxially oriented PET film. Furthermore, the end of the film is held by a clip and introduced into a hot air zone heated to 80 to 180°C, dried, and then stretched 2.5 to 5.0 times in the width direction. Subsequently, the film is introduced into a heat treatment zone at 160 to 240°C, where heat treatment is performed for 1 to 60 seconds to complete the crystal orientation. During this heat treatment process, a relaxation treatment of 1 to 12% may be performed in the width direction or longitudinal direction as necessary.
[0039] (Adhesive layer) The polyester film that is attached to the surface of the folding display to protect the surface of the display is adhered by an adhesive layer laminated on one surface of the polyester film. The adhesive layer can be made of any material, including rubber, acrylic, urethane, polyester, silicone, and the like, without any particular limitation. In addition, two or more types of materials can be mixed and used, or two or more layers can be used, as long as the optical properties are not affected. Particles such as fillers and additives can also be added.
[0040] (Adhesive layer thickness) The thickness of the adhesive layer is preferably 1 to 25 μm, more preferably 3 to 15 μm. If it is thicker than 1 μm, it has sufficient adhesive strength and does not peel off even when bent, which is preferable. If it is thinner than 25 μm, it is preferable because deformation of the adhesive when bent is suppressed and image distortion does not occur.
[0041] (Method of applying adhesive layer) The adhesive layer can be applied by any method including, but not limited to, a comma coater, a knife coater, a die coater, a gravure coater, a Mayer bar coater, etc., which can be appropriately selected depending on the viscosity and film thickness.
[0042] (Adhesive layer curing conditions) The method for curing the adhesive layer is not particularly limited and may be selected appropriately from methods using energy rays such as ultraviolet rays and electron beams, and heat.
[0043] (Hard coat layer) The polyester film that is attached to the surface of the foldable display to protect the surface of the display preferably has a hard coat layer on the surface opposite to the adhesive layer. The resin that forms the hard coat layer can be any of acrylic, siloxane, inorganic hybrid, urethane acrylate, polyester acrylate, and epoxy resins without any particular limitation. Two or more materials can be mixed and used, and particles such as inorganic filler and organic filler can be added.
[0044] (Thickness of hard coat layer) The thickness of the hard coat layer is preferably 1 to 40 μm. If the thickness is more than 1 μm, the hard coat layer is sufficiently cured and a good pencil hardness is obtained. Furthermore, by making the thickness 40 μm or less, curling due to cure shrinkage of the hard coat layer can be suppressed, and the handling properties of the film can be improved.
[0045] (Hard Coating Layer Coating Method) The hard coat layer can be applied by any method including, but not limited to, a Mayer bar coater, a gravure coater, a die coater, and a knife coater, and can be appropriately selected depending on the viscosity and film thickness.
[0046] (Hard Coat Layer Curing Conditions) The hard coat layer can be cured by energy rays such as ultraviolet rays and electron beams, or by heat, but ultraviolet rays and electron beams are preferred in order to reduce damage to the film.
[0047] (Pencil hardness) The pencil hardness of the hard coat layer is preferably B or more, more preferably H or more. If the hard coat layer has a pencil hardness of B or more, it is not easily scratched and does not reduce visibility. In general, the harder the hard coat layer has, the more preferable the pencil hardness is, but it may be 10H or less, 8H or less, or even 6H or less.
[0048] (Type of hard coat layer) The hard coat layer in the present invention may have other functions added thereto, so long as it can be used for the purpose of increasing the pencil hardness of the surface and protecting the display as described above.For example, hard coat layers with added functions such as antiglare layers, antiglare antireflection layers, antireflection layers, low reflection layers, and antistatic layers having a certain pencil hardness as described above are also preferably used in the present invention.
[0049] In the present invention, when a hard coat layer is laminated on the surface opposite to the side on which the adhesive layer is laminated of the polyester film, the total light transmittance of the hard coat layer is preferably 85% or more, more preferably 87% or more, similar to that of the polyester film. If the transmittance is 85% or more, it is preferable because visibility can be sufficiently ensured. In the above case, the higher the total light transmittance, the better, but it may be 99% or less, or 97% or less. EXAMPLES
[0050] Next, the effects of the present invention will be described using examples and comparative examples. First, the evaluation methods of the characteristic values used in the present invention will be described below.
[0051] (1) Intrinsic viscosity The film or polyester resin was crushed and dried, and then dissolved in a mixed solvent of phenol / tetrachloroethane = 60 / 40 (mass ratio). After the solution was centrifuged to remove inorganic particles, the flow time of a solution with a concentration of 0.4 (g / dl) at 30°C and the flow time of the solvent alone were measured using an Ubbelohde viscometer, and the intrinsic viscosity was calculated from the time ratio using the Huggins formula and assuming that the Huggins constant is 0.38. In the case of a laminated film, the intrinsic viscosity of each layer alone was evaluated by scraping off the corresponding polyester layer of the film according to the laminate thickness.
[0052] (2) Flexibility The adhesive surface of the sample is attached to a 50 μm thick polyimide film to prepare a measurement sample with a size of 50 mm in the width direction × 100 mm in the flow direction. Using a no-load U-shaped stretch tester (Yuasa System Co., Ltd., DLDMLH-FS), the bending radius is set to 3 mm, and the sample is bent 50,000 times at a speed of 1 time / second. At that time, the sample is fixed at a position 10 mm from both ends of the long side, and the bending area is 50 mm × 80 mm. After the bending process, the sample is placed on a flat surface with the inside of the bend facing down, and visually inspected. In each of the following examples and comparative examples, the bending resistance of the surface protection film with a hard coat layer is evaluated. ◎: No deformation of the sample was observed. ○: The sample was deformed, but the maximum floating height was less than 5 mm when placed horizontally. ×: The sample has a crease or the maximum height of the sample when placed horizontally is 5 mm or more.
[0053] (3) Pencil hardness The surface of the hard coat layer was measured in accordance with JIS K 5600-5-4:1999 at a load of 750 g and a speed of 0.5 mm / s.
[0054] (4) Total light transmittance, haze Measurement was performed using a haze meter (NDH5000, manufactured by Nippon Denshoku Industries Co., Ltd.) In each of the following examples and comparative examples, the total light transmittance and haze of the surface protection film with a hard coat layer were measured.
[0055] (5) Adhesive strength The adhesive side of the sample was attached to a SUS plate (SUS304), and a 2 kg rubber roller was rolled back and forth once, after which the sample was left at room temperature for 20 hours.The force (N / 25 mm) required to peel the adhesive tape from the SUS plate at an angle of 180° at a speed of 300 mm / min was measured using a tensile tester.
[0056] (Preparation of hard coat coating solution 1) 94.9 parts by weight of dipentaerythritol hexaacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., product name: A-DPH, solid content concentration: 100% by weight), 5 parts by weight of a photoradical polymerization initiator (manufactured by IGM Resins, product name: Omnirad907, solid content concentration: 100% by weight), and 0.25 parts by weight of a silicone additive (manufactured by BYK Japan, BYK-3505, solid content concentration: 40% by weight) were mixed and diluted with a solvent of MEK / toluene / IPA = 1 / 1 / 1 to prepare a 40% hard coat coating solution 1.
[0057] (Preparation of adhesive coating solution 2) 100 parts by weight of an acrylic adhesive (manufactured by Toyo Ink Mfg., product name: Olivine BPS5762K, solids concentration: 45.5% by weight), 1.4 parts by weight of a crosslinking agent (manufactured by Toyo Ink Mfg., product name: BXX5627, solids concentration: 50% by weight), and 30.6 parts by weight of MEK were mixed to prepare an adhesive coating solution 2 with a solids concentration of 35%.
[0058] (Preparation of adhesive coating solution 3) 100 parts by weight of a silicone adhesive (manufactured by Shin-Etsu Chemical Co., Ltd., product name: X-40-3237), 0.5 parts by weight of a catalyst (manufactured by Shin-Etsu Chemical Co., Ltd., product name: PL-50T), and 0.5 parts by weight of a crosslinking agent (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KS-3802) were diluted with toluene to prepare adhesive coating solution 3 with a solids concentration of 40%.
[0059] (Preparation of polyethylene terephthalate pellets (a)) A continuous esterification reactor consisting of a three-stage complete mixing tank having an agitator, a partial condenser, a raw material inlet, and a product outlet was used as the esterification reactor, and the slurry was continuously fed to the first esterification reactor of the esterification reactor with TPA at 2 tons / hr, EG at 2 moles per mole of TPA, and antimony trioxide at an amount such that Sb atoms were 160 ppm relative to the produced PET, and reacted at normal pressure for an average residence time of 4 hours at 255°C. Next, the reaction product in the first esterification reactor was continuously taken out of the system and fed to the second esterification reactor, and EG distilled from the first esterification reactor was fed to the second esterification reactor at 8% by mass relative to the produced polymer (produced PET), and further, an EG solution containing magnesium acetate in an amount such that Mg atoms were 65 ppm relative to the produced PET and an EG solution containing TMPA in an amount such that P atoms were 20 ppm relative to the produced PET were added, and reacted at normal pressure for an average residence time of 1.5 hours at 260°C. Next, the reaction product in the second esterification reactor was continuously taken out of the system and fed to a third esterification reactor, and an EG solution containing TMPA in an amount such that the P atom was 20 ppm relative to the produced PET was added, and the reaction was carried out at normal pressure for an average residence time of 0.5 hours at 260° C. The esterification reaction product produced in the third esterification reactor was continuously fed to a three-stage continuous polycondensation reactor to carry out polycondensation, and further filtered with a stainless steel sintered filter medium (nominal filtration accuracy of 90% cut of 5 μm particles) to obtain polyethylene terephthalate pellets (a) with an intrinsic viscosity of 0.62 dl / g.
[0060] (Preparation of polyethylene terephthalate pellets (b)) In the same manner as in the production process of polyethylene terephthalate pellets (a), except for adjusting the residence time of the third esterification reaction, the intrinsic viscosity was adjusted to 0.580 dl / g to obtain polyethylene terephthalate pellets (b).
[0061] (Preparation of polyethylene terephthalate pellets (c)) The polyethylene terephthalate pellets (a) were subjected to solid-phase polymerization at 220° C. for various times under a reduced pressure of 0.5 mmHg using a rotary vacuum polymerization apparatus to produce polyethylene terephthalate pellets (c) having an intrinsic viscosity of 0.67 dl / g.
[0062] (Preparation of polyethylene terephthalate pellets (d)) The polyethylene terephthalate pellets (a) were subjected to solid-phase polymerization at 220° C. for various times under a reduced pressure of 0.5 mmHg using a rotary vacuum polymerization apparatus to produce polyethylene terephthalate pellets (d) having an intrinsic viscosity of 0.75 dl / g.
[0063] (Preparation of polyethylene terephthalate pellets (e)) The polyethylene terephthalate pellets (a) were subjected to solid-phase polymerization at 220° C. for various times under a reduced pressure of 0.5 mmHg using a rotary vacuum polymerization apparatus to produce polyethylene terephthalate pellets (e) having an intrinsic viscosity of 0.83 dl / g.
[0064] The polyethylene terephthalate master pellets (a) were dried under reduced pressure (3 Torr) at 180°C for 8 hours, and then the polyethylene terephthalate pellets (a) were fed to an extruder and melted at 285°C. The polymer was filtered through a stainless steel sintered filter medium (nominal filtration accuracy 10μm particles 95% cut), extruded into a sheet from a die, and then contacted with a casting drum with a surface temperature of 30°C using an electrostatic casting method to cool and solidify, producing an unstretched film. The unstretched film was stretched 3.4 times in the longitudinal direction at 85°C. The uniaxially stretched film was stretched 4.2 times in the transverse direction at 95°C using a tenter, and heat-treated at 220°C for 5 seconds to obtain the polyethylene terephthalate film No. 1 in Table 1. The polyethylene terephthalate master pellets (b) to (e) were fed to a process similar to that described above, except for some adjustments to the conditions, to obtain the polyethylene terephthalate films No. 1 to 7 in Table 1.
[0065] Example 1 Hard coat coating solution 1 was applied to one side of polyethylene terephthalate film No. 4 using a Mayer bar so that the film thickness after drying would be 2.0 μm, and the film was dried at 80° C. for 1 minute, and then irradiated with ultraviolet light (accumulated light amount 200 mJ / cm 2 Next, the adhesive coating solution 2 was applied to the surface of the polyethylene terephthalate film on the side on which the hard coat layer was not laminated so that the film thickness after drying would be 10 μm, and the coating was dried at 120° C. for 1 minute to prepare a surface protection film.
[0066] Example 2 Hard coat coating solution 1 was applied to one side of polyethylene terephthalate film No. 4 using a Mayer bar so that the film thickness after drying would be 2.0 μm, and the film was dried at 80° C. for 1 minute, and then irradiated with ultraviolet light (accumulated light amount 200 mJ / cm 2 Next, the adhesive coating solution 3 was applied to the surface of the polyethylene terephthalate film on the side on which the hard coat layer was not laminated so as to have a film thickness after drying of 10 μm, and dried at 130° C. for 1 minute to prepare a surface protection film.
[0067] (Examples 3 to 5, Comparative Examples 1 to 3) A surface protection film was prepared under the conditions in Table 2 in the same manner as in Example 1.
[0068] [Table 1]
[0069] [Table 2] [Industrial Applicability]
[0070] According to the present invention, it is possible to provide a protective film for a folding display that is less likely to deform after the folding display is repeatedly folded and is less likely to cause image distortion over time.
Claims
1. a polyester film having a thickness of 50 to 75 μm, an intrinsic viscosity of 0.65 to 1.0 dl / g, and a total light transmittance of 87% or more, and an adhesive layer on one side of the polyester film; The polyester film is a biaxially oriented polyethylene terephthalate film, A hard coat layer is laminated on the side of the polyester film opposite to the side having the adhesive layer, In a no-load U-shaped stretch test in which the cable was bent 50,000 times at a bending radius of 3 mm and a speed of 1 time per second, A surface protection film for a folding display that, when placed horizontally on a flat surface with the inside of the bend facing down after bending, has a maximum lift of less than 5 mm or does not deform.
2. The adhesive layer is formed of an acrylic adhesive, The surface protection film for a folding display according to claim 1 , wherein the hard coat layer is formed of an acrylic resin.
3. An organic electroluminescence display; A touch panel disposed on the upper part of the organic EL display; A foldable display comprising: the surface protective film for a foldable display according to claim 1 or 2, which is disposed on an upper portion of a touch panel.
4. A mobile terminal device comprising the foldable display according to claim 3.
Citation Information
Patent Citations
Flexible plastic film
CN107849390A
Optical film
JP2008012834A
Laminated polyester film for optical use
JP2010214675A
Easily adhesive thermoplastic resin film
JP2011140543A
Hard coat film, curable resin composition for hard coat layer, and method for producing hard coat film
JP2014238614A